Network Analysis of Past Presidents of the North American Skull Base Society - Luebs, John K.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Little is known about the relative contributions and interactions of the past presidents of the North American Skull Base Society (NASBS) and skull base centers.Objectives (1) Measure academic contributions of past presidents; (2) identify influential nodes of academic collaboration; (3) identify opportunities for future collaboration.Methods Peer-reviewed publications of past presidents of NASBS from 1964 to July 2019 were identified using Scopus author name search. Network structures were constructed and analyzed using the graph-tool python library to produce a weighted co-authorship network base and compute centrality measures. Girvan–Newman clustering was applied to identify community structure. Network maps were then produced using Gephi network visualization software with force-directed layout algorithms.Results The coauthor network of 29 presidents was fully connected, with a maximum shortest-path distance between presidents of 5. The mean number of connections from each node without respect to weighting was 5.31 (standard deviation [SD]: 3.53), and the mean number of connections with weighting was 8.40 (SD: 7.28). The number of unweighted connections ranged from 1 to 14 and weighted connections ranged from 0.25 to 24.7. Girvan–Newman clustering identified three communities with two that covered 93% of the network. The largest communities contained 14 and 13 presidents. The number of connections was correlated with h-index, both unweighted (r2 = 0.34) and weighted (r2 = 0.26).Conclusion Network mapping of past presidents of the NASBS helps to capture the history of the NASBS and reveals areas of concentration and influence within the specialty.
Keywords: skull base; presidents; network; history